Company strategy and organizational design - Mansfield, Roger, 1942- (London : Routledge, 2013)
Getting strategies and structures right for changing market conditions and successfully matching strategies and structures with each other, are crucial. This volume reviews and develops the extensive literature in the areas of business policy and organizational behaviour, taking the subject further by breaking down boundaries between subject areas within management studies; by adopting a dynamic approach to organizational issues; and by synthesizing the disparate, often confusing research findings in this area into a general theoretical approach which can be assimilated by managers faced with the problems of the real world.
First published: 1986.
Bibliography : page 177-180.
Keywords: Organizational effectiveness; Organizational change; Strategic planning